Ivermectin and Gynecologic Cancer: What are the data? - Mujumdar, Vaidehi; Huang, Marilyn; Smith, Lindsey Chippendale; Musa, Fernanda (Gynecologic oncology reports, 2025)
•Ivermectin is currently approved by the US Food and Drug Administration (FDA) in 1996 as an oral medication for intestinal strongyloidiasis and onchocerciasis.•The data on ivermectin as a gynecologic cancer-fighting compound is lacking.•Clinical studies on ivermectin use in cancer are limited to effects observed in cell lines.•We have not assessed ivermectin’s safety and efficacy in gynecologic cancers.•We do not recommend and strongly caution the use of ivermectin in the treatment of gynecologic cancers.